EFFECTS OF EARLY MOBILIZATION EDUCATION ON PAIN INTENSITY AMONG POST-CAESAREAN PATIENTS AT PKU MUHAMMADIYAH BANTUL HOSPITAL OF YOGYAKARTA - Lutfi, Haerul; Murdiyanto, Joko (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Caesarean section surgery causes pain and results in changes to tissue continuity due to the incision. If such pain is not controlled, it can prolong the healing process and lead to complications in respiration, excretion, circulation, and other systemic functions. Early mobilization is necessary to promote blood circulation as soon as possible and to facilitate recovery or relief of post-operative pain following a Caesarean section. Objective: This study aimed to investigate the effects of early mobilization education on pain intensity among post-Caesarean section patients at PKU Muhammadiyah Bantul Hospital, Yogyakarta. Method: This study used quantitative method with pre-experimental design approach, specifically the one-group pretest-posttest design. The sampling technique was consecutive sampling, with 30 respondents who met the inclusion and exclusion criteria. Data collection was conducted using the VAS pain scale, and data analysis was done using the Wilcoxon signed-rank test. Results: The Wilcoxon signed-rank test results showed p-value 0.01 < α (0.05), which indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Pre-test results showed that the highest level of pain among post-Caesarean section patients was mild pain, experienced by 19 patients (63.3%). Meanwhile, post-test results indicated that all 30 patients (100%) experienced mild pain. Conclusion: Early mobilization education has a significant effect on reducing pain intensity among post-Caesarean section patients at PKU Muhammadiyah Bantul Hospital, Yogyakarta. Recommendations: Future researchers should conduct experimental or quasi-experimental studies to compare pain intensity between patients who receive early mobilization education and those who do not.